2016
DOI: 10.30657/pea.2016.13.10
|View full text |Cite
|
Sign up to set email alerts
|

Production of heterogeneous surfaces by ESD and LBM

Abstract: Abstract. The paper is concerned with testing Cu-Mo coatings deposited over carbon steel C45 which were then eroded with a laser beam. The properties were assessed by analyzing the effects of laser eroded, texturing methodology and wear tests. The tests were conducted for Mo and Cu coatings (the anode) which were electro-spark deposited over the C45 steel substrate (the cathode) and melted with a laser beam. The coatings were deposited by means of an ELFA-541. The laser processing was performed with an Nd:YAG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…By controlling the energy stream, we can process selected areas of a workpiece. The diameter of the spot of the influence of energy stream varies from a fraction of nanometers to several tens of centimeters [1,2]. It depends on the basic physical phenomenon occurring in a given technology [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…By controlling the energy stream, we can process selected areas of a workpiece. The diameter of the spot of the influence of energy stream varies from a fraction of nanometers to several tens of centimeters [1,2]. It depends on the basic physical phenomenon occurring in a given technology [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…cutters or drills, creates a number of possibilities for improving their functional properties. The demand for new, more durable and harder tools has resulted in the increased interest in new methods of heat treatment [1][2][3]. One of the methods of obtaining more supersaturated structures with a higher than in the conventional grain refining processing, which arise as a result of the action on high energy material in a short time is laser treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of a microstructured surface can be modified using chemical, thermal, mechanical or combined mechanical and thermal processes. The thermal processes include plasma spraying, electric arc spraying, sintering, laser surface texturing or electrical discharge texturing [7][8][9][10][11][12][13]. Very broad critical review of past achievements can be found in [14], where much room was devoted to discussing mathematical models and their application to numerical analysis.…”
mentioning
confidence: 99%